Research Collaboration with the Architectural Design Process: Co-Development of Problems and Solutions - Laiprakobsup, Narongpon (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This research aims to investigate what a possible framework design research can be integrated withthe architectural-design process. The process of design embodies dialectics between generation of form andresearch. How strategic design research is cooperative into design processes to achieve the design solutionhas been barely examined in a broad range of the architectural-design practices. The study thus explores acomparative analysis of the design processes in different design practice between third-year architecture students,fifth-year architecture students, and architects, to examine various forms of design research taking place infinding and solving problems. Findings reveal that design research lies in investigative modes and processing of external knowledgerelevant to problems, thereby enabling for a decisive solution. Research cooperates with the design process aslearning tensions between problems and solutions. However, the problem-solution pairing and research takingplace do not promise the successful solution. The acceptable design unfolds continuous improvement betweena series of problems-solutions through which research induces the co-development of problems-solutionsframework from an abstract idea to concrete levels of design development in three situations: “understandingcriteria and formulating goals,” “exploring possibility,” and “examining reality.” Moreover, practitioners mostly drawupon more design visions to direct problem-framing, research, and working methods to meet design goals thannovice students operate research into the process of design. To effectively implement research into the design process, a designer could consider design activity asa critical learning process as the co-development of problems-solutions framework to operate design strategiesand thinking. This mode of design thinking will allow design research roles to collaborate with problem-framingand design methods into the design process.